EFFECT OF BUCCAL CORRIDORS ON SMILE ESTHETIC IN DIFFERENT FACIAL TYPES AMONG THAI POPULATION - Charoenpong, Hataichanok; Sriarunotai, Suthapar; Sritangos, Apinya; Madnurak, Wirin; Ruangamnat, Nichakorn; Pimsupa, Onkamon; Chotesmithkul, Piyanut; Girddornfag, Panida; Thaprungsirikul, Paveena (Interprofessional Journal of Health Sciences, 2023)
Esthetic has become the major concerns for the majority of patients seeking orthodontic treatment. One factor that can affect attractiveness of the smile is buccal corridor size. Therefore this study aimed to evaluate the smile attractiveness of facial display in frontal view with different buccal corridor sizes and different facial types in Thai population. Using visual analog scale survey, facial display sets of selected male and female models with five different sizes of buccal corridors (2%, 10%, 15%, 22%, and 28%) in three different facial types (brachyfacial, mesofacial, and dolichofacial) were rated by the subjects. Subjects were 403 Thai laypersons (107 males and 296 females) aged between 18-40 years old from all geographic regions. The results indicated that, Thai people rated buccal corridor size of 15% as the most while the least attractive buccal corridor size was found to be 28% (the widest buccal corridor/the narrowest smile) for all facial type in both genders. Compared to the most attractive buccal corridor size, statistical analysis showed that the range of the buccal corridor size that did not compromise smiling attractiveness were 10-15% in mesofacial, 2-22% in brachyfacial, 10-15% in dolicofacial male and 10-22% in dolicofacial female.